Exploring Native Speakerism to Improve EFL Students' English Language Skills - Masruria, Wulida Wahidatul; Annisa, Zahra Kholifia (Paedagogie, 2026)
English has become the most widely spoken language among speakers of various languages all over the world (Wang & Fang, 2020). Therefore, the annual increase in individuals acquiring English is 12 (Schreiber, 2019). In recent years, native English teachers have been prioritized in English education in Indonesia (Zhang & Solarz, 2022) because of the language authenticity in the classroom. The concept of "native speakerism" indicates that native English teachers are the ideal teachers in language education (Holliday, 2006), while non-native English teachers are the least ideal English teachers. The purpose of this study is to analyze students' proficiency in NEST and NNEST classes, as well as to investigate their motivation and teacher preferences. The study comprised 50 eleventh-grade EFL learners from two courses at a high school in East Indonesia. A mixed method was used to complete the study. These included finding the average test scores before and after the study. The results were compared using paired sample t-tests and semi-structured interviews. The objective was to ascertain whether this method could enhance students' motivation and preferences for English skills. The findings revealed that students instructed by native English teachers excelled in speaking competencies, whereas those educated by non-native English teachers performed better in written abilities, especially grammar. The purpose of this study is to raise awareness of "native speakerism" among students and teachers, and it provides various research implications for enhancing English instruction and student learning.